Firefighters at the B. F. Huntley Furniture Company fire, 1956. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 2-15-56 p.1.
Firefighters at the B. F. Huntley Furniture Company fire, 1956. The company was located at 1201 N. Patterson Avenue.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth